An Observational Cohort Study and Nested Randomized Controlled Trial on Nutrition and Growth Outcomes in Moderate and Late Preterm Infants (FLAMINGO) - Kakaroukas, Andreas; Abrahamse-Berkeveld, Marieke; Berrington, Janet E.; McNally, Richard J. Q.; Stewart, Christopher J.; Embleton, Nicholas D.; van Elburg, Ruurd M. (Frontiers in Nutrition, 2021)
Background: Over the past decades, the preterm birth rate has increased, mostly due to a rise in late and moderate preterm (LMPT; 32-36 weeks gestation) births. LMPT birth affects 6-7% of all births in the UK and is associated with increased morbidity risk after birth, in infancy as well as in adulthood. Early life nutrition has a critical role in determining infant growth and development but there are limited data specifically addressing LMPT infants, which was the rational for the design of the current study. Objective: The FLAMNINGO study aims to improve understanding of the longitudinal growth, nutritional needs and body composition of LMPT infants, as well as their microbiome development and neurodevelopment. In addition, having a nested non-inferiority trial, enables evaluation of the nutritional adequacy of a concept IMF with large, milk phospholipid coated lipid droplets comprising dairy and vegetable lipids. The primary outcome of this RCT is daily weight gain until 3 months corrected age. Methods A total of 250 healthy LMPT infants (32+0 – 36+6 weeks gestational age) with birth weight 1.25-3.0 kg will be recruited to the cohort, of which 140 infants are anticipated to be enrolled in the RCT. During six visits over the first 2 years of life, anthropometry, body composition (using Dual Energy X-Ray Absorptiometry), feeding behaviour and developmental outcomes will be measured. Saliva and stool samples will be collected for oral and gut microbiota assessment. Discussion: The FLAMINGO study will improve understanding of the longitudinal growth, body composition development and feeding characteristics of LMPT infants and gain insights in their microbiome and neurodevelopment.